2012
DOI: 10.1246/cl.2012.774
|View full text |Cite
|
Sign up to set email alerts
|

Silane(silyl) and Bis(silyl)hydrido Manganese Complexes with Different Mn···H···Si Interaction: Observation of Gradual Si–H Bond Activation on the Metal Center

Abstract: Three manganesecarbonyl complexes having a xanthenebased silane(silyl) or bis(silyl) chelate ligand were synthesized and characterized. The single-crystal X-ray analysis of these complexes demonstrated that an SiH bond is sequentially activated on the metal according to ligand substitution of CO with xanthene-oxygen or η 6 -toluene.The SiH bond activation of hydrosilanes induced by transition-metal complexes is an attractive process for its broad application to the synthesis of organosilicon compounds (e.g., h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 15 publications
2
22
0
1
Order By: Relevance
“…Complex 4a is the first structurally characterized disilyl hydride complex of manganese with nonchelating silyl ligands, although Tobita et al previously reported a series of disilyl hydride and silyl hydrosilane complexes in which both silicon-based donors are tethered by a xanthene backbone (Figure ). The Mn–Si distance of 2.3851(2) Å in 4a is within the range previously observed for manganese silyl hydride complexes (2.254(1)–2.4702(9) Å) and is shorter than those in Tobita’s most closely related disilyl hydride complex ( T3 in Figure : d (Mn–Si) = 2.4026(7)–2.4069(7) Å) …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Complex 4a is the first structurally characterized disilyl hydride complex of manganese with nonchelating silyl ligands, although Tobita et al previously reported a series of disilyl hydride and silyl hydrosilane complexes in which both silicon-based donors are tethered by a xanthene backbone (Figure ). The Mn–Si distance of 2.3851(2) Å in 4a is within the range previously observed for manganese silyl hydride complexes (2.254(1)–2.4702(9) Å) and is shorter than those in Tobita’s most closely related disilyl hydride complex ( T3 in Figure : d (Mn–Si) = 2.4026(7)–2.4069(7) Å) …”
Section: Resultssupporting
confidence: 84%
“…35 The Mn−Si distance of 2.3851(2) Å in 4a is within the range previously observed for manganese silyl hydride complexes (2.254(1)−2.4702(9) Å) 36 and is shorter than those in Tobita's most closely related disilyl hydride complex (T3 in Figure 5: d(Mn−Si) = 2.4026(7)−2.4069(7) Å). 35 The central position of the hydride ligand between the two silyl ligands in 4a,b appears to be maintained on the NMR time scale in solution, given that the 1 H NMR spectra indicate C 2 symmetry between 25 and −87 °C. In the solid state (for 4a), the Si(1)−H(1A) distance is 1.9163(8) Å (calculated 1.92 Å), which is significantly longer than a typical Si−H single bond (1.48 Å) 37 but much shorter than the sum of the van der Waals radii (3.1 Å).…”
Section: ■ Results and Discussionsupporting
confidence: 81%
“…From its positive/negative slope one can conclude that the individual 1 J (Si,H t ) and J (Si,H br ) coupling constants are of same/opposite sign in 2 and 5 , respectively . Since 1 J (Si,H t ) < 0, the sign of J (Si,H br ) must be negative (−63 Hz) in 2 and positive (+15 Hz) in 5 .…”
Section: Resultsmentioning
confidence: 99%
“…From its positive/negative slope one can conclude that the individual 1 J(Si,H t ) and J(Si,H br ) coupling constants are of same/opposite sign in 2 and 5, respectively. 90 Since 1 J(Si,H t ) < 0, 17 the sign of J(Si,H br ) must be negative (−63 Hz) in 2 and positive (+15 Hz) in 5. 3 and reflect again the promotion of the oxidative addition of the Si−H bond to the metal atom by electron-withdrawing substituents at the silicon atom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation